2011
DOI: 10.1002/cb.362
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging children to eat more healthily: The influence of packaging

Abstract: The objective of this study was to understand how food packaging can influence children's attitudes and purchase decisions toward healthier choices. The appealing components of junk food packaging were transferred onto healthy food in order to test its effect on children's package evaluation, attention to packaging attitude toward the product, perceived healthiness and purchase intention. A structured questionnaire was completed by a sample of 408 Portuguese children aged between 10 and 14 years. Findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…The increasing prominence of food placements on television (see Elliott, ; Pires & Agante, ; Speers et al ., ; Sutherland et al ., ) stands in sharp contrast to the scarce empirical evidence in the literature. Although there is some knowledge about the effects of brand placements on children's cognitive, affective, and conative responses to online games (e.g., Harris, Speers, Schartz, and Brownell, ; Mallinckrodt & Mizerski, ; Pempek & Calvert, ; van Reijmersdal, ), none of this research is dedicated to food consumption behavior or food intake as a consequence of exposure to placements in narrative movies.…”
mentioning
confidence: 99%
“…The increasing prominence of food placements on television (see Elliott, ; Pires & Agante, ; Speers et al ., ; Sutherland et al ., ) stands in sharp contrast to the scarce empirical evidence in the literature. Although there is some knowledge about the effects of brand placements on children's cognitive, affective, and conative responses to online games (e.g., Harris, Speers, Schartz, and Brownell, ; Mallinckrodt & Mizerski, ; Pempek & Calvert, ; van Reijmersdal, ), none of this research is dedicated to food consumption behavior or food intake as a consequence of exposure to placements in narrative movies.…”
mentioning
confidence: 99%
“…This helps ensure that users' preferences with respect to graphical design, shape, size, and packaging materials are effectively identified so the designer can use these preferences to achieve the required users' responses. For example, dietary foods can be packaged with more appealing packages to attract children and affect their attitudes …”
Section: At the Point Of Purchasementioning
confidence: 99%
“…For example, dietary foods can be packaged with more appealing packages to attract children and affect their attitudes. 99 Since this review focuses on only the primary aspects of product packaging, the visual attributes of shape, size, color, labels, logos, signs, and brand are all the graphics that can be seen by users as they interact with the primary package. An overview of the research related to these aspects can be found in Table 1.…”
Section: Visual Attributesmentioning
confidence: 99%
“…Prior research regarding food consumption, obesity, consumers' behaviour and nutrition knowledge has focused mainly in consumers' perceptions of the healthiness of food items in a menu restaurant (Burton et al, 2006); the effect of age in the understanding of food labels (Cole and Gaeth, 1990;Burton and Andrews, 1996); consumers' search and use of nutrition information at the grocery store (Carrillo et al, 2012;Grunert et al, 2012;Balasubramanian and Cole, 2002;Russo et al, 1986;Müller, 1985); the use of visual cues to regulate food intake (Madzharov and Block, 2010;Wansink et al, 2005); and, children perception of packages, their understanding of nutrition labels and their consumption behaviour while eating at fast food places (Grier and Moore, 2012;Miller et al, 2011;Pires and Agante, 2011;Sttuts et al, 2011). Balasubramanian and Cole (2002) stated that to fight the obesity battle and to comply with norms such as the Nutrition Labeling and Education Act from the USA, nutrition research should focus also in all purchase and eating occasions not only in packaged food bought at a retail store; and, considering that consumers are relying on computers to gather information in an efficient form, research should also include how technology is being used by consumers in making more informed choices; therefore, with this study we try to find if motivated consumers are willing to use their handheld devices (i.e., smartphones) to gather information at the point of food consumption before making their choices in order to select food items that provide a more healthy option.…”
Section: Food Consumption Habitsmentioning
confidence: 99%